Engineering Molecular Topology: A Pseudopeptidic Macrocyclic Figure‐Eight Motif. Issue 7 (12th December 2016) - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P; Butcher, Ray; Haridas, V.
Abstract : We herein present a rational‐design strategy for the synthesis of molecules with figure‐eight topology. The design concept is based on the incorporation of turn units in the backbone of the macrocycle. The molecular structures and the folding are studied by X‐ray crystallography and NMR, FT‐IR, and CD spectroscopy. Abstract : We herein present a strategy for the synthesis of macrocyclic hybrid peptides with unusual topological features. The macrocycles have a rigid cavity and twisted figure‐eight motif and are synthesized based on a bicyclic‐turn inducing bispidine scaffold.